BIAYA DAN PRODUKTIVITAS PENYARADAN DAN PEMBUATAN/PEMELIHARAAN KANAL DI HTI RAWA GAMBUT DI RIAU DAN JAMBI - Sona Suhartana; Yuniawati; Dulsalam (BRIN Publishing, 2013)
Productivity and cost of skidding and canal establishment are important activity on timber harvesting in peat swamp forest plantation. It could determine timber harvesting efficiency. A study was carried out in June 2011 at concession area of Arara Abadi Company, Riau and July 2011 at Wirakarya Sakti Company, Jambi. This study aimed to find out productivity and cost of skidding and canal establishment at peat swamp forest plantation. Field data i.e. productivity and cost of skidding and canal establishment were collected and processed by tabulation. Study result revealed that 1. The average of skidding productivity for plot I, II, and III each are 12,42; 13,77; 15,32, m/bour (Jambi) and 11,46; 13,04: 15,13 mi/hour (Riau), 2. The average of skidding, cast for Plott I, II, and III rach are Rp 28.306/m², Rp 25.483/mi, Rp 22.843/m (Jambi) and Rp 30.592/m², Rp 26.834/mi, Rp 23.158/m² (Riau), and 3. The average of canal establishment cost for Plats I, II, and III each are Rp 13.623/m, Rp 13.189/m, Rp 13.048/m (Jambi) and Rp 9.670/m. Rp 9.630/m, Rp 9.431/m (Riau).